Chemotherapy Induced Radiation Recall Injury (KYAMC Journal, 2020)
Radiation recall is characterized by an acute inflammatory reaction confined to previously irradiated areas that is triggered by the administration of precipitating systemic agents after radiation treatment. The most common responsible drugs are anticancer agents, but other drugs can also cause radiation recall including some antibiotics, antitubercular drugs, simvastatin can also cause radiation recall phenomenon. We report a case of paclitaxel induced radiation recall injury in a 57 year old male with carcinoma left lung with brain metastases.KYAMC Journal Vol. 11, No.-3, October 2020, Page 158-160